IMPLEMENTASI KOMPETENSI GURU DALAM PENILAIAN PEMBELAJARAN (Penilaian Afektif Dalam Dunia Pendidikan) - Muli Prima Aldi (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2020)
The teacher is one of the important elements that must exist after the students. If a teacher does not have a professional attitude, students will find it difficult to grow and develop properly. This is because teachers are one of the foundations for the state in terms of education. With the existence of professional and quality teachers, it will be able to produce quality children of the nation as well. The key that every teacher must have is competence.